Hepatitis E Virus Antibodies in Patients with Chronic Liver Disease - Atiq, Muslim (Centers for Disease Control and Prevention, 2009)
In the United States, the seroprevalence rate for hepatitis E virus (HEV) is ≈20%. This study examined HEV seroprevalence in persons with and without chronic liver disease. Our data indicate that HEV seropositivity is high in patients with chronic liver disease and that HEV seroprevalence increases significantly with age.